Supply Chain Digitalization and Performance: The Serial Mediation of Visibility and Resilience - Thi Thanh Nhan Tran; Anh Duc Do; Minh Ngoc Nguyen (Emerging Science Journal, 2026)
This study aims to examine how supply chain digitalization enhances supply chain performance through the serial mediation of supply chain visibility and supply chain resilience. Grounded in the Resource-Based View and Dynamic Capabilities Theory, the research model was empirically tested using survey data collected from 379 managers of manufacturing firms operating in Vietnamese industrial parks. The data was analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that supply chain digitalization positively influences both visibility and performance. However, while visibility improves performance when examined independently, its direct effect becomes insignificant once resilience is incorporated, suggesting that visibility alone is insufficient to achieve superior performance without strong resilience capabilities. Moreover, the serial mediation path digitalization → visibility → resilience → performance was statistically significant, confirming the sequential mechanism through which digitalization improves performance outcomes. The study contributes to the literature by clarifying the complementary roles of visibility and resilience and highlighting resilience as the key capability linking digitalization to performance. From a managerial perspective, the results emphasize that investing in digital technologies should be accompanied by initiatives to strengthen resilience capabilities to maximize the benefits of digital transformation in supply chains.